Experimental Study of Prevention and Control of Rock Burst in Steeply Inclined Coal Seams by Mining Sequence and Filling - Zhihui Zhang; Yangyi Liu; Wenwen Zhu; Jian Liu; Tian Ma; Chunxue Xie (Shock and Vibration)
The control and prevention of rock burst in a steeply inclined coal seam are essential. In order to figure out the effects of filling and mining sequence on rock burst in the steeply inclined coal seam, B3+6 and B1+2 coal seams in Wudong coal mine are chosen as the research objects, and an in-house experiment system of similarity simulation is established in this study. Combined with numerical simulation, the characteristics of collapse, stress distribution, and displacement variations can be measured, which provide useful information to study the effects of the filling body and mining sequence on rock burst. Experimental results show that the key reason for rock burst in a steeply inclined coal seam is the stress concentration of the rock pillar between B3+6 and B1+2 coal seams instead of the stress-lever-effect of a deeper rock pillar. The filling body can support the middle rock pillar, share the geological structure stress in the horizontal and vertical direction, eliminate the stress concentration zone largely, and prevent the occurrence of rock burst. When multiple working faces are working, the opposite side of the coal seam should be mined first to release the energy in the rock in advance, thus preventing the rock burst effectively. The research results provide fundamental information for better understanding the reason for rock burst and preventing rock burst in the steeply inclined coal seam.